2014
DOI: 10.1007/s00415-014-7603-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cognitive dysfunction during migraine attacks: a systematic review

Abstract: Patients consistently report cognitive impairment during migraine attacks, yet the documentation of such dysfunction by neuropsychological evaluation has lacked similar consistency. This incongruence may be due to discrepant study designs, assessment tools and small samples sizes. To search for evidence of decline in cognitive functions during a migraine attack, compared to headache-free performance. The secondary objective was to determine if the eventual decline had a consistent neuropsychological pattern. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 35 publications
8
34
0
Order By: Relevance
“…The large proportion with ictal aural symptoms agrees with the frequency (up to 69%), usually tinnitus, reported by others . Reversible cognitive dysfunction, reported by some of our patients, is a known feature of migraine attacks . Fatigue (13.7% of our patients) was also observed in another VM study …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The large proportion with ictal aural symptoms agrees with the frequency (up to 69%), usually tinnitus, reported by others . Reversible cognitive dysfunction, reported by some of our patients, is a known feature of migraine attacks . Fatigue (13.7% of our patients) was also observed in another VM study …”
Section: Discussionsupporting
confidence: 92%
“…4,10,13,17,18,[20][21][22]27,31 Reversible cognitive dysfunction, reported by some of our patients, is a known feature of migraine attacks. 32 Fatigue (13.7% of our patients) was also observed in another VM study. 22 Vestibular symptoms were not limited to VM attacks, but also occurred interictally.…”
Section: Discussionsupporting
confidence: 84%
“…Bearing in mind that subjective cognitive complaints correlate with objective deficits in neuropsychological tests in the general population, our findings corroborate previous documentation of reversible pre‐frontal and executive difficulties during migraine attacks . Several executive measurements – such as Trail B and Wisconsin, alternate finger tapping, visual‐spatial SWITCH task, and in the Boston Scanning Test and Controlled Oral Word Association Test (but not in Trail B) – documented a decline in migraineurs compared to controls.…”
Section: Discussionsupporting
confidence: 89%
“…Migraine is a common brain disorder with a strong vascular involvement that is characterized by recurrent severe headache and may be accompanied by light sensitivity or gastrointestinal discomfort. In clinical practice, patients with migraine commonly complain of cognitive impairment . The prevalence of migraine is higher among patients with silent brain lesions .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, patients with migraine commonly complain of cognitive impairment. 1,2 The prevalence of migraine is higher among patients with silent brain lesions. 3 Sgaramella et al 4 reported that patients with migraine perform worse on prospective memory tests than those without migraine.…”
Section: Introductionmentioning
confidence: 99%